2017
DOI: 10.1038/s41564-017-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for maintenance of bacterial outer membrane lipid asymmetry

Abstract: The Gram-negative bacterial outer membrane (OM) is a unique bilayer that forms an efficient permeation barrier to protect the cell from noxious compounds . The defining characteristic of the OM is lipid asymmetry, with phospholipids comprising the inner leaflet and lipopolysaccharides comprising the outer leaflet . This asymmetry is maintained by the Mla pathway, a six-component system that is widespread in Gram-negative bacteria and is thought to mediate retrograde transport of misplaced phospholipids from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
172
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(185 citation statements)
references
References 70 publications
7
172
0
6
Order By: Relevance
“…The soluble, periplasmic substrate binding protein Ttg2D and its orthologs in other species are thought to transport mislocalized phospholipids from the outer leaflet of the outer membrane (OM) to the inner membrane (IM) complex Ttg2ABCE across the periplasm 21 . In P. aeruginosa , it is not yet known if the VacJ component of the system, which delivers the lipids to Ttg2D, forms a complex with specific porins, as in E. coli , to extract the lipids from the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The soluble, periplasmic substrate binding protein Ttg2D and its orthologs in other species are thought to transport mislocalized phospholipids from the outer leaflet of the outer membrane (OM) to the inner membrane (IM) complex Ttg2ABCE across the periplasm 21 . In P. aeruginosa , it is not yet known if the VacJ component of the system, which delivers the lipids to Ttg2D, forms a complex with specific porins, as in E. coli , to extract the lipids from the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our work, it has been previously shown that in P. aeruginosa, VacJ plays an important role in both virulence and antibiotic susceptibility to ciprofloxacin, chloramphenicol and tetracycline 74 . In E. coli , this protein forms an active complex with the outer membrane proteins OmpC and OmpF 21, 23, 75 . However, in P. aeruginosa there are no clear orthologs to either of these porins, increasing the singular characteristics of this system in this species and suggesting potential mechanistic differences with the more studied E. coli transporter (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst it has been well established that a host of PLs can move in a retrograde fashion from the OM to the IM (Jones and Osborn 1977), it remains unclear as to how PLs travel in the opposite direction. It has been suggested that retrograde PL transport is in part driven by the action of the OM MlaA-OmpF/C system (Abellon- Ruiz, Kaptan et al 2017). In fact, Thong et al (2016) proposed that the MlaFEDB driven hydrolysis of ATP may provide the necessary energy to indirectly remove PLs from the OM against their concentration gradient.…”
Section: Discussionmentioning
confidence: 99%
“…It was described as having a role in maintaining lipid asymmetry in the OM by removing and trafficking PLs found in the outer leaflet of the OM to the IM (Malinverni and Silhavy 2009). Through genetic knockouts, structural and modelling-based studies, the individual components have been identified and characterised ( Figure 1) (Chong, Woo et al 2015, Thong, Ercan et al 2016, Abellon-Ruiz, Kaptan et al 2017, Ekiert, Bhabha et al 2017, Yeow, Tan et al 2018.…”
Section: Introductionmentioning
confidence: 99%